(3GOGQI GdLhOI GdTGedI hGdGfJGLjI hGdJNWjW GdJcfhdhLj ddJejR hGdQjGOI hGdJahb (B/s - (3GdfLGQ, aQjOs ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2007)
(3GdEfJGLjI hGdJbOe,efXheGJ GdLhOI hGdJejR haYGdjGJ GdJbOe,GdJejjR hGdJbOe hGdJWhjQ GdeSJeQs
(3HHdhZQGajG(B:(3U(B.522-524s
Keywords: (3EOGQI GdEfJGLs; (3LhOI GdEfJGLs